1999
DOI: 10.1089/088922299311097
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Choice Reaction Time Performance in SIV-Infected Rhesus Macaques

Abstract: It is well established that HIV infection can lead to motor/cognitive disorders in humans. A number of studies have shown that simian immunodeficiency virus (SIV) infection in rhesus macaques parallels many aspects of HIV disease in humans. The purpose of this study was to define further the SIV-infected rhesus macaque as a model of neuro-AIDS. Our objective was to detect movement-related impairments in behaviorally trained, SIV-infected macaques using both simple and choice reaction time tasks. Reaction times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The motor skill declines documented in this paper, together with impairments on simple and choice reaction time tasks in the same monkeys reported earlier [26], support the contention that the motor system is a target of SIV infection in rhesus macaques. Reaction time (RT) and movement time (MT) deficits were comparable to those found in HIV patients.…”
Section: Other Primate Studiessupporting
confidence: 85%
“…The motor skill declines documented in this paper, together with impairments on simple and choice reaction time tasks in the same monkeys reported earlier [26], support the contention that the motor system is a target of SIV infection in rhesus macaques. Reaction time (RT) and movement time (MT) deficits were comparable to those found in HIV patients.…”
Section: Other Primate Studiessupporting
confidence: 85%
“…Neurological complications such as increased cognitive deficits and behavioral impairments have been shown in HIV-infected subjects dependent on opiates compared to HIV-infected non-drug abusers (Bell et al, 1996; Chiesi et al, 1996; Bell et al, 1998; Goodkin et al, 1998; Nath et al, 2001; Bell et al, 2006; Anthony et al, 2008; Hellmuth et al, 2014) and in SIV infected macaques (Marcario et al, 1999a; Marcario et al, 1999b; Fox et al, 2000; Weed and Gold, 2001; Weed et al, 2003; Weed et al, 2004; Cheney et al, 2008). Previous studies from our group have shown that morphine potentiates neuropathognesis in macaques infected with SIV mac R71/17E (Marcario et al, 2008; Bokhari et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…SIV-infected animals exhibit altered functional integrity of motor and sensory pathways as well as impaired behavioral performance with the progression of disease (Gold et al, 1998; Horn et al, 1998; Marcario et al, 1999a, b; Murray et al, 1992; Prospero-Garcia et al, 1996; Raymond et al, 1998; Raymond et al, 1999; Raymond et al, 2000; Weed et al, 2004). In previous studies using a cohort of SIV mac R71/17E inoculated rhesus macaques, we demonstrated that ABR and VEP peak latency shifts generally correlate with underlying neuropathology at the level of the auditory brainstem nuclei and visual pathway structures (Raymond et al, 1998; Raymond et al, 2000).…”
Section: Introductionmentioning
confidence: 99%